An in vitro evaluation of the effects of Urtica dioica and Fructus Urtica Piluliferae extracts on the crystallization of calcium oxalate - POLAT, SEVGİ (ELSEVIER, 2019)
This study investigated crystallization of calcium oxalate in the presence of Urtica dioica and Fructus Urtica Piluliferae extracts. To evaluate the structures, morphologies and phase transformations of the crystals, X-ray diffraction, Raman and Fourier-transform infrared spectroscopy, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were used. The results showed that both additives exerted significant effects on the crystallization process. When Fructus Urtica Piluliferae was used as an additive, the products were a mixture of the monohydrate and dihydrate forms of calcium oxalate. Both SEM and TEM confirmed that the crystals contain different morphologies including hexagonal prismatic and tetragonal bipyramidal forms. The addition of Urtica dioica to the crystallization medium led to the formation of the monohydrate form being efficiently inhibited with only the dihydrate crystals of calcium oxalate being formed over 30 days. A change in the morphology of the crystals from hexagonal prismatic to round nanocrystals was detected in the Urtica dioica medium. Moreover, zeta potential measurements showed that the surface of the crystals became more negative when compared with those prepared from the pure medium with the value increasing from -3.2 +/- 0.5 to -40 +/- 4.6 mV. This study demonstrated the modification of the structure and morphology of calcium oxalate crystals as well as the inhibition of its monohydrate form were possible using Urtica dioica and Fructus Urtica Piluliferae.
Keywords: Calcium oxalate; Crystallization; Crystal Morphology; Urtica dioica; Fructus Urtica Piluliferae; CRYSTAL-GROWTH; THERMAL-TREATMENT; EPITHELIAL-CELLS; URINARY CALCULI; MONOHYDRATE; INHIBITION; DIHYDRATE; RAMAN; KIDNEY; MORPHOLOGY